2012
DOI: 10.1016/s0020-7292(12)60012-5
|View full text |Cite
|
Sign up to set email alerts
|

Public hospital costs of treatment of abortion complications in Nigeria

Abstract: Unsafe abortion is a significant contributor to maternal mortality in Nigeria, and treatment of postabortion complications drains public healthcare resources. Provider estimates of medications, supplies, and staff time spent in 17 public hospitals were used to estimate the per-case and annual costs of postabortion care (PAC) provision in Ogun and Lagos states and the Federal Capital Territory. PAC with treatment of moderate complications (US $112) cost 60% more per case than simple PAC (US $70). In cases needi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…According to KIIs, less than 1% of safe abortions and 6% of PAC cases require major surgeries or dialysis. A study in Nigeria found similar estimates (1% of all PAC cases) and did not include these costs in their calculations (Benson et al, 2012). Since such complications are predominantly in the unsafe abortion group, by not including these costs, our estimates for the cost of PAC for unsafe abortions are probably underestimated as compared to safe abortion.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…According to KIIs, less than 1% of safe abortions and 6% of PAC cases require major surgeries or dialysis. A study in Nigeria found similar estimates (1% of all PAC cases) and did not include these costs in their calculations (Benson et al, 2012). Since such complications are predominantly in the unsafe abortion group, by not including these costs, our estimates for the cost of PAC for unsafe abortions are probably underestimated as compared to safe abortion.…”
Section: Discussionmentioning
confidence: 72%
“…Zambia has high levels of unmet need for contraception (CSO, 2014), and evidence from Nigeria has shown how additional investment in family planning can lead to large net benefits from reduced expenditure in PAC services (Benson, Okoh, KrennHrubec, Lazzarino, & Johnston, 2012). A similar conclusion was reached in a study from Uganda, where investing in contraception would cost six times less than investing in PAC for unsafe abortion (Vlassoff, Mugisha, et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…A modified Delphi approach was used to solicit information from the providers using a standardized questionnaire adapted from tools for estimating PAC costs in Nigeria and Malawi [8]. The form captured details about the steps taken from admission to discharge to treat a single case of incomplete abortion at a public health facility.…”
Section: Estimates Of Pac Costsmentioning
confidence: 99%
“…An additional 62 million US dollars estimated annual economic costs are incurred due to treatment of long-term, abortion-related health effects [2]. Multiple studies have consistently found that unsafe abortion leads to a high burden of morbidity and mortality and significant costs to public health systems in Africa [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Vlassoff et al [20] analyzed a survey of 14 public and private health facilities in Ethiopia and found that the average total cost of postabortion treatment per patient was US $36, and the cost–benefit ratio if contraception was provided to help women avoid unintended pregnancy is 6:1 (for every dollar spent on contraception, $5 are saved on postabortion care costs). In Nigeria, Benson et al [21] found that the cost of postabortion care for patients with moderate complications is 60% higher than the cost for patients with the least serious complications, and that the cost of using manual vacuum aspiration (MVA) is lower than the use of dilatation and curettage (D&C). In a study in Bangladesh, Johnston et al [22] also found that providing postabortion care with MVA is less expensive than using D&C. The paper highlights the importance of permitting midlevel providers to offer postabortion care and provide postabortion contraceptive counseling and services.…”
mentioning
confidence: 99%